Pneumatosis cystoides intestinalis- a morphological curio or a pitfall for surgeons: report of two cases and literature review - Bode, Anjali N.; Poflee, Sandhya V.; P, Nandu P. Pande; Shrikhande, Anuradha V. (International Journal of Research in Medical Sciences, 2017)
Pneumatosis Cystoides Intestinalis (PCI) is an uncommon but well recognised clinical entity in which gas-filled cysts appear in the intestinal wall.PCI can be an incidental finding or it may be detected during radiography or laparotomy. We came across two cases of PCI with characteristic morphological features associated with perforation peritonitis in and sigmoid volvulus respectively. In both cases PCI was not suspected pre-operatively.Both patients underwent urgent surgical exploration for the abdominal emergencies and were discharged in good general condition. It is imperative that the imaging finding of PCI is carefully correlated with the findings of physical examination, clinical history, and laboratory test results to determine which patients can be managed medically by treating the underlying disease and which will require emergency surgery. This decision can be difficult because the origin of the gas is often unclear and the patient’s symptoms can be volatile, presenting a major dilemma for the surgeon.